Meningkatkan Pemahaman Siswa pada Mata Pelajaran PPPKn melalui Model Problem Based Learning (PBL) di Kelas 1 SDN 067240 Medan Tembung - Maulidya Nurliana; Zainal Azis; Enniy Purba (Lembaga Yasin AlSys, 2025)
This study is motivated by the often monotonous teaching of Pancasila and Citizenship Education (PPPKn) in elementary schools, which tends to reduce students’ motivation to think critically and solve problems. An innovative learning model is needed to improve students’ understanding and interest. The objective of this research is to enhance the understanding and learning outcomes of Grade I students in PPPKn through the application of the Problem Based Learning (PBL) model at SD Negeri 067240 Medan Tembung. The study employed a Classroom Action Research (CAR) method conducted over two weeks in the even semester of the 2025 academic year, from 7 to 22 March 2025, involving 21 Grade I students. The research object was PPPKn learning outcomes after implementing the PBL model. The results show that a PBL approach designed to be enjoyable for students improved academic performance, with the average score increasing from 71.81 in cycle I to 80.52 in cycle II. The percentage of students achieving mastery also rose from 62% in cycle I to 86% in cycle II, surpassing the success indicator of 80% of students meeting the Minimum Mastery Criteria (Kriteria Ketuntasan Minimal, KKM). These findings demonstrate that the PBL model is effective in improving PPPKn understanding and learning outcomes in elementary school students.